2021
DOI: 10.1007/s10904-021-01991-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Treatment of Pd-Cr@Carbon for Efficient Oxygen Reduction Reaction in Proton-Exchange Membrane Fuel Cells

Abstract: A nanostructured PdCr@carbon catalyst is deposited on a supported carbon surface using the modified polyol reduction method for the oxygen reduction reaction (ORR) for the application in the proton exchange membrane fuel cell. The crystal structure and feature nanostructure of the PdCr@carbon were established using the XRD and TEM, while their catalytic activity was studied using the cyclic voltammetry and electrochemical polarization techniques. The estimated average crystallite size of PdCr is increased with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Up to date, several strategies have been developed to improve the electrocatalytic properties of Pd. The previous literature has reported that alloys of Pd with other metals (such as Cu [9], Pt [15], Co [16], Ag [17], Au [18], Sn [19], Ni [20], Rh [21], Zn [22], Pb [23], Cr [24], and Ir [25]) can not only enhance catalytic activity, but also improve the corrosion resistance of Pd. In particular in Pd-Pt alloys, the electronegativities and bulk Wigner-Seitz radii of Pt and Pd are similar [26].…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, several strategies have been developed to improve the electrocatalytic properties of Pd. The previous literature has reported that alloys of Pd with other metals (such as Cu [9], Pt [15], Co [16], Ag [17], Au [18], Sn [19], Ni [20], Rh [21], Zn [22], Pb [23], Cr [24], and Ir [25]) can not only enhance catalytic activity, but also improve the corrosion resistance of Pd. In particular in Pd-Pt alloys, the electronegativities and bulk Wigner-Seitz radii of Pt and Pd are similar [26].…”
Section: Introductionmentioning
confidence: 99%